The apudessive in Lithuanian - Petit, Daniel (Vilnius University Open Series, 2022)
The paper describes the rise of the apudessive preposition pàs in Lithuanian. The apudessive meaning (‘at someone’s home’) was rare in Old Lithuanian, where pàs denoted spatial proximity in competition with priẽ. The preposition pàs underwent a multi-stage evolution [behind] > [adessive] (first only directional) > [adessive] (both directional and positional) > [apudessive] (both directional and positional).
Keywords: Lithuanian; Old Lithuanian; prepositions; adessive; apudessive